2020
DOI: 10.3390/cancers12071943
|View full text |Cite
|
Sign up to set email alerts
|

Pre-Treatment Mutational and Transcriptomic Landscape of Responding Metastatic Melanoma Patients to Anti-PD1 Immunotherapy

Abstract: Immunotherapy, such as anti-PD1, has improved the survival of patients with metastatic melanoma. However, predicting which patients will respond to immunotherapy remains a significant knowledge gap. In this study we analyzed pre-immunotherapy treated tumors from 52 patients with metastatic melanoma and monitored their response based on RECIST 1.1 criteria. The responders group contained 21 patients that had a complete or partial response, while the 31 non-responders had stable or progressive disease. Whole exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 55 publications
2
33
1
Order By: Relevance
“…The analysis revealed that expression of baseline NLRP3/IL-1β levels do not consistently correlate with the IFN-γ signature, which have been positively linked to anti–PD-1 efficacy in melanoma patients. Nevertheless, analysis from the Amato et al ( 43 ) study ( SI Appendix , Fig. S7 ) shows a trend of increased expression of NLRP3 and IL-1β in the nonresponders, suggesting a dysregulation of IL-1β and NLRP3 in these patients.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The analysis revealed that expression of baseline NLRP3/IL-1β levels do not consistently correlate with the IFN-γ signature, which have been positively linked to anti–PD-1 efficacy in melanoma patients. Nevertheless, analysis from the Amato et al ( 43 ) study ( SI Appendix , Fig. S7 ) shows a trend of increased expression of NLRP3 and IL-1β in the nonresponders, suggesting a dysregulation of IL-1β and NLRP3 in these patients.…”
Section: Discussionmentioning
confidence: 95%
“…We examined three published clinical studies that employ anti–PD-1 treatment in patients with melanoma ( 41 43 ). The analysis revealed that expression of baseline NLRP3/IL-1β levels do not consistently correlate with the IFN-γ signature, which have been positively linked to anti–PD-1 efficacy in melanoma patients.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the PRJEB23709 and GSE145996 datasets were used for validation. 20 , 21 Sample information for the 5 abovementioned datasets is listed in Supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Bulk and single-cell transcriptomic analyses of tumor specimens obtained from patients before and after anti-CTLA4 and/or anti-PD1 administration, have unequivocally demonstrated that the up-regulation of NF-κB-dependent genes in both tumor and immune cells, underlies the clinical response to checkpoint-blockade therapies [ 169 , 170 ]. In particular, a number of supposedly NF-κB-regulated cytokines and chemokines are up- and down-regulated in patients who respond to immunotherapy [ 171 ].…”
Section: Nf-κb Modulation At the Era Of Immunotherapy: Activationmentioning
confidence: 99%